Charge carrier concentration optimization of thermoelectric p-type half-Heusler compounds - Rausch, Elisabeth; Balke, Benjamin; Deschauer, Torben; Ouardi, Siham; Felser, Claudia (APL Materials, 2015)
The carrier concentration in the p-type half-Heusler compound Ti0.3Zr0.35Hf0.35CoSb1-xSnx was optimized, which is a fundamental approach to enhance the performance of thermoelectric materials. The optimum carrier concentration is reached with a substitution level x = 0.15 of Sn, which yields the maximum power factor, 2.69 × 10-3 Wm-1K-2, and the maximum ZT = 0.8. This is an enhancement of about 40% in the power factor and the figure of merit compared to samples with x = 0.2. To achieve low thermal conductivities in half-Heusler compounds, intrinsic phase separation is an important key point. The present work addresses the influence of different preparation procedures on the quality and reproducibility of the samples, leading to the development of a reliable fabrication method.
CRIS-Team Scopus Importer:2023-03-20